DIGITALIZATION AND TELEMEDICINE IN COLOPROCTOLOGY AS STEPS TOWARD THE FORMATION OF A MODERN SYSTEM OF SPECIALIZED CARE IN UZBEKISTAN - Matkarimov Sanjarbek Rahimboyevich; Abdusattarov Khurshid Abdusamatovich; Sa'dullayev Samariddin Ulug‘bek o‘g‘li (Western European Studies, 2025)
In the context of a shortage of specialized personnel and unequal access to coloproctological care in Uzbekistan, digitalization and telemedicine are emerging as critical directions for healthcare modernization. This narrative review explores the potential of digital technologies to improve accessibility, quality, and clinical effectiveness of specialized services. The study focuses on the pilot implementation experience at the Multidisciplinary Clinic of the Center for Professional Development of Medical Personnel, which introduced digital patient routing, automated diagnostics, histological-laboratory integration, and remote consultations. The findings reveal a reduction in diagnostic delays, increased treatment adherence, and higher patient satisfaction. The analysis supports the conclusion that digital tools serve a system-forming role and should be prioritized as a strategic axis of coloproctology reform in Uzbekistan
Keywords: telemedicine; digital health; coloproctology; patient routing